2022
DOI: 10.3390/ani12050584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Dietary Regimes on the Gut Microbiota and Fecal Metabolites of Père David’s Deer

Abstract: A deep understanding of the effect of seasonal dietary changes on the nutrition and health of Père David’s deer in Dafeng Reserve will contribute greatly to Père David’s deer’s protection. In this reserve, there were three seasonal dietary regimes: feeding on naturally occurring plants (PLANT diet), silage (SILAGE diet), and a combination of natural plants and silage (COMB diet). To some extent, the COMB diet reflects the seasonal transition from silage to the all-natural plant diet, especially in early spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…A healthy intestinal barrier is characterized by the selective permeability of nutrients, metabolites, water, and bacterial products, while processes are governed by cellular, neural, immune, and hormonal factors [ 37 ]. The gut microbiota of Père David’s deer was mostly composed of Firmicutes and Bacteroidetes, at >90% of the total community [ 2 ]. We showed that the Firmicutes to Bacteroidetes ratio (2.73) decreased in diarrheic animals when compared with healthy animals (3.47), but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A healthy intestinal barrier is characterized by the selective permeability of nutrients, metabolites, water, and bacterial products, while processes are governed by cellular, neural, immune, and hormonal factors [ 37 ]. The gut microbiota of Père David’s deer was mostly composed of Firmicutes and Bacteroidetes, at >90% of the total community [ 2 ]. We showed that the Firmicutes to Bacteroidetes ratio (2.73) decreased in diarrheic animals when compared with healthy animals (3.47), but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then vortexed, sonicated, and centrifuged at 12,000 rpm for 10 min at 4 °C. The supernatant was filtered through a 0.2 µm filter and then 150 μL sample was used for UPLC-MS/MS (MS/MS, QTRAP ® , AB Sciex, Framingham, MA, USA) analysis as previously [ 2 ]. Linear ion trap (LIT) and triple quadrupole (QQQ) scans were acquired on a QQQ-linear ion trap MS, equipped with an electrospray ionization (ESI).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations